The Effect of Small Deficiency in Calcium Ion on Structural and Magnetic Properties in La0.7Ca0.15□0.05Sr0.1MnO3 with Various Synthesis Methods - Nehan, Phahul Zhemas Zul; Naibaho, Marzuki; Febrianti, Yeni; Widakdo, Januar; Manawan, Maykel; Darminto, Darminto; Kurniawan, Budhy (Trends in Sciences, 2025)
We have investigated the effect of a small calcium ion deficiency and different synthesis methods on the structural and magnetic properties of the La0.7Ca0.15□0.05Sr0.1MnO3 compound. The samples were synthesized using solid-state, sol-gel, and wet-mixing methods. Structural analysis revealed that all samples exhibited a single-phase orthorhombic crystal structure with the Pnma space group. The lattice parameters and the MnO6 octahedral structure changed based on the synthesis method and slight deficiency, leading to structural distortion and a mixed-valence state of Mn ions. The average crystallite sizes were 75.79, 113.98, and 107.23 nm, while the average grain sizes were 3.41, 2.06, and 1.29 μm for solid-state, sol-gel, and wet-mixing samples, respectively. FTIR confirmed the primary MnO6 octahedral structure through Mn-O and Mn-O-Mn bonds at wavenumbers of 513 - 539 and 590 - 591 cm−1. Magnetic measurements revealed the highest magnetization values of 29.50, 42.58, and 33.37 emu/g at room temperature under a 1 T magnetic field. In the meantime, the values of saturation magnetization were 37.11, 46.49, and 40.09 emu/g, as determined by the Law of Approach to Saturation method. Based on the structural and magnetic results, the sol-gel method produced the largest crystallite size and the lowest material defect level (smallest microstrain), resulting in the highest magnetization at room temperature under a 1 T magnetic field. These findings demonstrate a strong correlation between synthesis method, structural parameters, and magnetic properties. HIGHLIGHTS Effect of Ca deficiency and synthesis methods on structural & magnetic properties. Crystallite size 75 - 114 nm and grain size 1.3 - 3.4 µm depending on method. All samples have soft magnetic properties. Crytallite size, grain size, and defect on material influencing magnetic properties. GRAPHICAL ABSTRACT